THE HEAVIEST SENTENCING FOR THE LEGAL SUBJECT OF CORRUPTION CRIME PERPETRATOR - Oksidelfa Yanto (Universitas Suryakancana, 2022)
This study uses a normative juridical research method through literature study by collecting secondary data. In this study, it was found that the discussion about corruption never ends. Legal subjects that can be held accountable come one after another. The legal subject in this case is